The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1164/rccm.200909-1462oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 Governs Allergen-induced Mast Cell Numbers in the Lung and Chronic Remodeling of the Airways

Abstract: Rationale-IL-9 is a pleiotropic cytokine that has multiple effects on structural as well as numerous hematopoietic cells, which are central to the pathogenesis of asthma.Objectives-The contribution of IL-9 to asthma pathogenesis has thus far been unclear, due to conflicting reports in the literature. These earlier studies focused on the role of IL-9 in acute inflammatory models; here we have investigated the effects of IL-9 blockade during chronic allergic inflammation.Methods-Mice were exposed to either prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(175 citation statements)
references
References 55 publications
5
165
1
3
Order By: Relevance
“…However, the mechanism how IL-9 works on ICCs remains unclear. A possible theory about the mechanism may be that IL-9 promotes the proliferation and SCF secretion of mast cells [22] . Then SCF combines with the c-Kit on the surface of ICCs and results in the activation of downstream signaling pathways, which regulate the growth and repair of ICCs [23] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism how IL-9 works on ICCs remains unclear. A possible theory about the mechanism may be that IL-9 promotes the proliferation and SCF secretion of mast cells [22] . Then SCF combines with the c-Kit on the surface of ICCs and results in the activation of downstream signaling pathways, which regulate the growth and repair of ICCs [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IL-9 is involved in the pathogenesis of human asthma (8,10,22,(37)(38)(39)(40). Indeed, monoclonal antibodies to IL-9 are currently being evaluated in asthma clinical trials (41).…”
Section: Human Th9 Cell Differentiation Is Also Regulated By Cox-2-dementioning
confidence: 99%
“…CD4 1 T helper cell subsets, which include T helper cell type 1 (Th1), Th2, and Th17 cells, are key components of the adaptive immune response in rodents and humans (1,(5)(6)(7). Allergic responses in the lung are traditionally thought of as being Th2 mediated; however, recent studies have shown that IL-9 contributes to allergic responses by promoting mast cell expansion and production of IL-13, which stimulates the release of mucus and contributes to airway hyperresponsiveness (1,5,8,9). Serum IL-9 levels, which correlate with symptom severity in patients with allergic rhinitis, depend on exposure to a causal allergen (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…IL-9 functions in multiple potential asthmatic roles, from promoting mast cell growth and development to initiating IL-4 expression and subsequent Bcell production of allergic antibodies. IL-9 has also been evaluated for its use as an asthma biomarker given its heightened expression in the lungs of asthmatic patients [61].…”
Section: Interleukinsmentioning
confidence: 99%